QUANTIFIER ALL DALAM KALIMAT BAHASA INGGRIS - Retno Widi Utami; Fatimah Djajasudarma; Eva Tuckytasari; Dudih A. Zuhud (Jurnal Sosioteknologi, 2010)
This paper deals with quantifier "žall"Ÿ as the effect of context-dependence. We propose that the lack of context understanding on quantification without restriction violate the sentences. The result shows that epistemic modality, can repair such sentences because they can serve as the restriction for the quantificational force of another expression.Basides modal verbs there exist other expressions of modality refferred to as modal expressionsor stance markers, such as always, usually, or often. This expressions will help speakers to limit the amount of their assertion about their knowledge, bilief, or opinion. Key words: all, quantifier, modals, semantic, restriction